Español - Zambrano U., H. Marcelo (Nawi, 2018)
The present article exposes characteristics and properties of digital images that oppose to current proposals that celebrate the overcoming of mechanistic social orders and highlight the possibilities opened by the present technological era, in which human beings produce, distribute and consume visual representations. The objective is to develop theoretically these characteristics to enrich and improve discussions about articulation between digital images and technology.